A cadaveric study in endoscopic 3D visualization of posterior fossa neurovascular complexes. (3rd June 2015) - Klironomos, G; Khan, O; Mansouri, A; Ebinu, J; Gonen, L; Radovanovic, I; Zadeh, G
Abstract : Background: The use of 3D endoscopy for posterior fossa surgery gradually adopted. In this study we compare the 3D to classic 2D endoscopy in evaluating neurovascular complexes in posterior fossa. Methods: Twenty retrosigmoid craniotomies, with a maximal diameter of 2cm were performed under neuronavigation on 10 fresh cadaveric heads. The posterior fossa dura matter was opened with a C-shaped incision and the base of the dural flap was placed over the sigmoid sinus. We used 3D and 2D endoscopes, with 0 and 45 degree angulations, connected to high definition camera lenses for optimal visualization of posterior fossa structures. Results: The superior, middle and inferior neurovascular complexes of the cerebellopontine angle were better visualized with 3D comparing to 2D endoscope. A detailed view of the porus trigeminous and structures associated with the tentorial incisura was also attained with 3D endoscopy. Conclusion: The high quality and resolution obtained by 3D endoscopy makes it a potentially valuable surgical and teaching tool in the armamentarium for endoscopic posterior fossa surgery. The stereoscopic view of the critical neurovascular structures of the posterior fossa, offered by 3D images, allows for a more detailed dissection in the difficult area of the cerebellopontine angle.